Pengaruh Leverage dan Likuiditas terhadap Profitabilitas Perusahaan Asuransi Syariah di Indonesia - M. Yusril Aziz; Hendra Harmain; Purnama Ramadani Silalahi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this research is to see how leverage (measured by Debt to Equity Ratio) and liquidity (measured by Current Ratio) affect profitability (measured by Return on Equity) in Indonesian Sharia Insurance Companies. The independent variables in this research are Debt to Equity Ratio and Current Ratio, while the dependent variable is Return on Equity. The data analyzed comes from the company's annual financial reports from 2017 to 2021. The research results show a simultaneous test result or F test of 7.129 with a sig value of 0.000. Fcount 7.129 > Ftable 2.76 with a sig value of 0.00 < 0.05 indicates that the hypothesis in this research or H1 can be accepted which states that the Debt to Equity Ratio and Current Ratio both have a significant influence on Return On Equity. The research results show that.